VARIATION IN HEALTH PROMOTING COMPOUNDS OF BLUEBERRY FRUIT ASSOCIATED WITH DIFFERENT NUTRIENT MANAGEMENT IN A SOILLESS GROWING SYSTEM - Milivojević, Jasminka M.; Radivojević, Dragan D.; Maksimović, Vuk M.; Dragišić Maksimović, Jelena J. (Journal of Agricultural Sciences (Belgrade), 2020)
The objective of this study was to determine and compare the content of total anthocyanins (TACY), total phenolics (TPC) and total antioxidant activity (TAA) of the fruit of ‘Bluecrop’ highbush blueberry grown under different nutrient management in a soilless production system. Field study was carried out in highbush blueberry plantation situated near Belgrade (Serbia), during the period of 2016-2017. The orchard was planted in the spring of 2016 in 50 l polypropylene pots with 5-year-old nursery plants. Each pot was filled with the mix of pine sawdust (60%), white peat (30%) and perlite (10%), and placed at distance of 0.8 m within the row and 3.0 m between the rows (4,170 bushes ha−1). The following fertilizer treatments were evaluated: 1. organic fertilizers (Org); 2. mineral fertilizers (Min) and 3. combination of organic and mineral fertilizers (Org-Min). Soluble NPK fertilizers were applied with irrigation water, whereas granulated mineral and pelleted organic fertilizers were mixed with the substrate. Fruit samples were collected in triplicate at the beginning, full maturity and at the end of harvest season. No significant effect of harvest time on each of tested parameters was observed, whereas content of TACY did not differ either affected by the fertilizer treatments. TPC in the fruit significantly increased in Org and Org-Min treatments (139.8 and 139.3 mg eq GA/100 g FW, respectively) compared to Min treatment (122.7 mg eq GA/100 g FW), while considarably high TAA level was found only in berries from Org - Min treatment (0.53 mg asc/g FW).